Examination Of Uric Acid Levels And Counseling In Ngaglik Village Batu City, East Java - Aris Widiyanto; Santy Irene Putri; Joko Tri Atmojo; Prima Soultoni Akbar; Retno Dewi Prisusanti; Asruria Sani Fajriah; Rina Tri Handayani (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: Uric0acid0is0a0produc0of0purine0metabolism. There are several causes of gout, including changes in diet, consumption of drugs, and alcohol consumption. The purpose of implementing this community service activity is to provide education to the community in Ngaglik Village and to check uric acid levels. Based on the team's observations on several residents in Ngaglik Village, it was found that most residents did not have sufficient knowledge about gout and did not carry out routine health checks. Methods: In order to increase awareness and understanding of residents about health care efforts, especially preventing gout, the team coordinated with the urban village to carry out community service activities in Ngaglik Village, Batu City, East Java. The target in implementing this program is all residents in the Ngaglik Village, Batu City. Community service activities were carried out on April 6, 2021, attended by the village head and also village officials and babinsa. Results: The result that has been achieved in this service is that all of the people present have undergone examination and counseling. Conclusion: After carrying out the activity, it is hoped that the community can follow up on the results of the examination and improve the behavior of efforts to prevent gout.